Antigen-Specific Treatment Modalities in MS: The Past, the Present, and the Future - Derdelinckx, Judith; Cras, Patrick; Berneman, Zwi N.; Cools, Nathalie (Frontiers in Immunology, 2021)
Antigen-specific therapy for multiple sclerosis may lead to a more effective therapy by induction of tolerance to a wide range of myelin-derived antigens without hampering the normal surveillance and effector function of the immune system. Numerous attempts to restore tolerance towards myelin-derived antigens have been made over the past decades, both in animal models of multiple sclerosis and in clinical trials for multiple sclerosis patients. In this review, we will give an overview of the current approaches for antigen-specific therapy that are in clinical development for multiple sclerosis as well provide an insight into the challenges for future antigen-specific treatment strategies for multiple sclerosis.